Cardinal Martini (1927-2012), pastor, guide and light of a risen Church - Verdoy, SJ, Alfredo (Razón y fe, 2018)
Our society and our Church are running short of credible witnesses. However, the recently deceased Cardinal Martini was, without a doubt, one of those witnesses. He was able to combine and provide his brilliant intelligence and the goodness of his heart in the service of our society and our Church. Enlightened by the Word of God, he ended up being pastor, guide and light of a risen Church.
Keywords: Cardinal Martini; Church; World; pastor; guide; light; Bible